Footprint of export-related GHG emissions from Latin America and the Caribbean - Kun Li (Inter-American Development Bank (IDB), 2021)
To quantify the growth in GHG emissions related to international trade, we build an extensive database for export-related production and transportation GHG emissions covering 189 countries and 10 sectors from 1990 to 2014. We employ this database to quantify the contribution of production and international transportation to total export-related GHG emissions from Latin America and the Caribbean and decompose growth in these to contributions of the increase in the regions trade flows, shifts in the composition of trade partners, changes in the traded product basket, and technological progress.
Keywords: Q56; F18; 330; Export-related GHG emissions; emission intensity; international trade by transportation mode